AI-Generated Content and Perceived Personalization on Purchase Intention of Generation Z: The Mediating Role of Brand Credibility - Hadiansyah Ma'sum; Ratih Hurriyati; Heny Hendrayati; Mokh Adib Sultan; Amirul Afif Muhamat (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study examines the effects of AI-Generated Content and Perceived Personalization on Purchase Intention, with Brand Credibility as a mediating variable, in the context of digital marketing. A quantitative approach was employed using primary data collected from 168 respondents across several provinces in Indonesia. The data were analyzed using Structural Equation Modeling (SEM) with AMOS to test the proposed hypotheses and relationships among variables. The results indicate that AI-Generated Content and Perceived Personalization significantly influence Brand Credibility, and that Brand Credibility also significantly influences Purchase Intention. Furthermore, AI-Generated content directly affects Purchase Intention. However, Perceived Personalization does not have a direct effect on Purchase Intention; instead, it influences Purchase Intention indirectly through Brand Credibility, indicating a full mediation effect. These findings highlight the important role of Brand Credibility in bridging digital marketing strategies and consumer behavior. Therefore, companies should optimize AI-driven content while strengthening brand credibility to enhance consumers' purchase intent, whereas personalization strategies should focus on building consumer trust.